Evaluation of the reliability and validity of the health regulatory focus scale in Chinese samples - Lyu, Xiaokang; Yang, Tingting; Fan, Yanqin; Hong, Haijuan; Fu, Chunye (Frontiers in Psychology, 2023)
This study sought to validate the psychometric properties of the Health Regulatory Focus Scale (HRFS), emphasizing its manifestation and association with personality traits in a Chinese context. Originally developed by Ferrer, the HRFS gauges individuals' inclinations either to avoid negative health outcomes (prevention focus) or achieve positive health outcomes (promotion focus). Our cross-sectional analysis involved a diverse sample of 652 Chinese participants, averaging 39.6 years in age (SD = 9.39). Data were analyzed using SPSS and AMOS, and both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were employed to assess the HRFS's factor structure. Additionally, we evaluated convergent and discriminant validity, criterion-related validity, internal consistency reliability, and test-retest reliability. The CFA results [CFI = 0.985, TLI = 0.971, RMSEA = 0.059, and SRMR = 0.047], combined with McDonald's omega value (0.916) and the test-retest correlation coefficient (0.78) for the HRFS, underscore its robust construct validity and reliability.Furthermore, the promotion dimension of the HRFS exhibited significant positive correlations with all dimensions of the Chinese Adjectives Short Scale of Big-Five Factor Personality (BFFP-CAS-S). In conclusion, the HRFS's Chinese adaptation offers a reliable and valid instrument for assessing health regulatory focus.